Normative model for the diagnosis of neuropsychiatric disorders using deep learning methods - Saraiva, Duarte Filipe Oliveira (2022)
Tese de mestrado integrado, Engenharia Biomédica e Biofísica (Engenharia Clínica e Instrumentação Médica) Universidade de Lisboa, Faculdade de Ciências, 2021